2012
DOI: 10.1097/dcr.0b013e3182538f14
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Stimulation for Fecal Incontinence Related to External Sphincter Atrophy

Abstract: Sacral nerve stimulation can be effective in restoring continence and improving quality of life in patients with fecal incontinence related to atrophy of the external anal sphincter, regardless of the severity of atrophy. Moreover, the presence of EAS atrophy does not influence the success of the outcome of SNS in patients with a sphincter defect. These findings are consistent with the hypothesis that the effects of SNS are not achieved solely by its action on the anal sphincter complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Seventy‐two full‐text articles were assessed in detail and a further 11 studies were excluded: one study used mixed urinary and faecal incontinence indications for implantation, one study did not have original clinical outcome data, two studies had PNE data only, three studies had no documented baseline of the chosen outcome measures, two studies had no follow‐up terms documented, one study did not clearly document the results of the chosen outcome measures and one study was excluded as it exactly duplicated the data set of another included study; further clarification was not possible. This left 61 SNS studies that were appropriate for inclusion; in order to present data on ITT analysis, studies were separated into those that included all consecutive patients (including failures) in whom PNE was attempted (46 studies) ( Table ) and those that only reported outcomes of positively responding patients to the test phase (15 studies) ( Table ). Patients who were still awaiting permanent implantation despite a successful PNE were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy‐two full‐text articles were assessed in detail and a further 11 studies were excluded: one study used mixed urinary and faecal incontinence indications for implantation, one study did not have original clinical outcome data, two studies had PNE data only, three studies had no documented baseline of the chosen outcome measures, two studies had no follow‐up terms documented, one study did not clearly document the results of the chosen outcome measures and one study was excluded as it exactly duplicated the data set of another included study; further clarification was not possible. This left 61 SNS studies that were appropriate for inclusion; in order to present data on ITT analysis, studies were separated into those that included all consecutive patients (including failures) in whom PNE was attempted (46 studies) ( Table ) and those that only reported outcomes of positively responding patients to the test phase (15 studies) ( Table ). Patients who were still awaiting permanent implantation despite a successful PNE were excluded from the analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Sacral neuromodulation 6.6.1. Indications for sacral neuromodulation Sacral Neuromodulation (SNM) can be considered for patients with FI with intact but weak anal sphincters or those with sphincter disruption up to 120 degrees of circumference [196,[233][234][235][236][237][238][239]. The presence of EAS atrophy does not influence the outcome of SNM in patients with a sphincter defect [240].…”
Section: Expert Panel Recommendationmentioning
confidence: 99%
“…One of the earliest studies to demonstrate efficacy of SNS in FI patients with a sphincter defect was a five patient series in which the authors describe progression to full continence in three. In a larger series of 28 FI patients with sonographic evidence of sphincter atrophy including 28% with evidence of an external sphincter defect , the CCF‐FIS decreased from a median of 16–3 ( P < 0.001), with demonstrable improvements seen in the subgroup of patients with a sphincter defect.…”
Section: Discussionmentioning
confidence: 88%